2019
DOI: 10.3390/coatings9090559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wet Expansion Behavior on Polyimide Membrane Diffractive Lens

Abstract: Optical polyimide (PI) membrane is a potential substrate to fabricate a diffractive primary lens in large aperture space-borne telescope. In this paper, we investigated the wet expansion behavior of PI via a strain gauge method and measured the coefficient of wet expansion (CWE) of PI membrane supported by different fixtures. The CWE of silica-fixed, ring-fixed, and free state PI membrane were near zero, 5 ppm/%, and 10 ppm/% respectively. It is found that Fresnel zone lens (FZL), based on PI membrane with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These homemade PI membranes were synthesized by 1,2,4,5-Benzenetetracarboxylic anhydride and 2,2′-Bistrifluoromethylbenzidine, and formed homogeneous film by multiple spin coats and imidization. Young’s modulus is about 7 GPa, and the transmittance is more than 80% at 632.8 nm [ 9 ]. In order to keep the PI membrane dimensionally stable and minimize the distortion of the etched pattern, the PI membrane substrates were fixed on a special circular tooling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These homemade PI membranes were synthesized by 1,2,4,5-Benzenetetracarboxylic anhydride and 2,2′-Bistrifluoromethylbenzidine, and formed homogeneous film by multiple spin coats and imidization. Young’s modulus is about 7 GPa, and the transmittance is more than 80% at 632.8 nm [ 9 ]. In order to keep the PI membrane dimensionally stable and minimize the distortion of the etched pattern, the PI membrane substrates were fixed on a special circular tooling.…”
Section: Methodsmentioning
confidence: 99%
“…In order to facilitate the measurement of etch depth, a diffractive micro-structure mask pattern using a photoresist (AZ1500) was exposed on the PI membrane substrate before RIE. The photolithography process mainly includes spin coating photoresist on the PI substrate, exposure and development, hard bake, dry etching and cleaning the PI substrate [ 9 ]. During the etching process, an additional electrode made of aluminum alloy (2A12) was placed under the PI membrane substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical PI membrane is a promising isotropic material for large-aperture-membrane diffractive lenses applied in next-generation space telescopes [11]. Recent research on transmissive diffractive membrane optics for large lightweight optical telescopes showed that the PI membrane easily deformed in-plane, resulting in failure of accurate light focusing [12,13]. The deformation of the PI membrane is accompanied by stress distribution variation, but it is difficult to quantitatively investigate how stress distribution changes during this process without inflicting damage [14][15][16].…”
Section: Introductionmentioning
confidence: 99%